Remotely Garden Irrigation for Residential Area Based on Internet of Things (IoT) - Lita Lidyawati; Lisa Kristiana; Arsyad Ramadhan Darlis; Lucia Jambola; Ratna Susana (Institut Teknologi Nasional, Bandung, 2020)
Activities such as planting and gardening become one of prominent hobbies. An issue of having such well grown plants is the impractical and unachieavable task to monitor 24 hours a day, thus we need a smart gardening system that can monitor the garden on demand. One of the problems in residential gardening systems is how to water the plants while the owner is not at home. Some of people have an adequate knowledge of using IoT to make their life easier. This paper proposes a simple automatic gardening system in watering several plants as programmed. In addition, this system allows human’s manual intervention either locally or remotely via Internet, to control a water pump. To build this smart gardening system, we use Xiaomi home application from Google Play. In this application, we can set the program to water the plants daily with definite time periodic independently.